Recessive PKD1 Mutations Are Associated With Febrile Seizures and Epilepsy With Antecedent Febrile Seizures and the Genotype-Phenotype Correlation - Wang, Jing-Yang; Wang, Jie; Lu, Xin-Guo; Song, Wang; Luo, Sheng; Zou, Dong-Fang; Hua, Li-Dong; Peng, Qian; Tian, Yang; Gao, Liang-Di; Liao, Wei-Ping; He, Na (Frontiers in Molecular Neuroscience, 2022)
Objective The PKD1 encodes polycystin-1, a large transmembrane protein that plays important roles in cell proliferation, apoptosis, and cation transport. Previous studies have identified PKD1 mutations in autosomal dominant polycystic kidney disease (ADPKD). However, the expression of PKD1 in the brain is much higher than that in the kidney. This study aimed to explore the association between PKD1 and epilepsy. Methods Trios-based whole-exome sequencing was performed in a cohort of 314 patients with febrile seizures or epilepsy with antecedent febrile seizures. The damaging effects of variants was predicted by protein modeling and multiple in silico tools. The genotype-phenotype association of PKD1 mutations was systematically reviewed and analyzed. Results Eight pairs of compound heterozygous missense variants in PKD1 were identified in eight unrelated patients. All patients suffered from febrile seizures or epilepsy with antecedent febrile seizures with favorable prognosis. All of the 16 heterozygous variants presented no or low allele frequencies in the gnomAD database, and presented statistically higher frequency in the case-cohort than that in controls. These missense variants were predicted to be damaging and/or affect hydrogen bonding or free energy stability of amino acids. Five patients showed generalized tonic-clonic seizures (GTCS), who all had one of the paired missense mutations located in the PKD repeat domain, suggesting that mutations in the PKD domains were possibly associated with GTCS. Further analysis demonstrated that monoallelic mutations with haploinsufficiency of PKD1 potentially caused kidney disease, compound heterozygotes with superimposed effects of two missense mutations were associated with epilepsy, whereas the homozygotes with complete loss of PKD1 would be embryonically lethal. Conclusion PKD1 gene was potentially a novel causative gene of epilepsy. The genotype-phenotype relationship of PKD1 mutations suggested a quantitative correlation between genetic impairment and phenotypic variation, which will facilitate the genetic diagnosis and management in patients with PKD1 mutations.